An analysis of business incubation: case study of Chemin business incubator in East London - Mnqokoyi, Zoliswa (Rhodes University, Faculty of Commerce, Rhodes Business School)
This study delves into an in-depth analysis of business incubation practices, focusing on the case study of Chemin Business Incubator located in East London. The primary aim of this research is to explore how Chemin utilizes both tangible and intangible resources to support incubates throughout the incubation process. Through a meticulous examination of resource allocation strategies, this study seeks to uncover the impact of these resources on the success of incubated ventures. Adopting a qualitative research design, the study employed a single case study approach, which enabled the researcher to explore in depth the resource utilization and allocation processes at Chemin. The research was conducted within the interpretivist paradigm, focusing on understanding the experiences of incubates and the management team. Data were collected through semi-structured interviews with 15 participants, including five entrepreneurs who successfully completed the incubation process, five entrepreneurs currently undergoing incubation, and five members of the management team. Additionally, document analysis of official Chemin documents provided secondary data to supplement the primary data collected through interviews. The research objectives included analyzing the allocation of resources to meet enterprise development goals, exploring the role of resources in determining incubate success at different stages of incubation, and identifying instances where resource allocation posed challenges to incubate success. Thematic analysis was used to analyze the collected data, identifying key themes and patterns related to resource allocation and its impact on incubate success. The findings of this study shed light on the multifaceted nature of resource utilization within the business incubation context. Tangible resources, including physical assets and financial support, were found to be instrumental in providing startups with essential infrastructure and funding networks. Additionally, intangible resources such as mentorship, networking opportunities, and business advisory services emerged as critical factors in nurturing entrepreneurial talent and fostering innovation. Moreover, the study identified key areas where resource allocation strategies could be optimized to enhance incubate success. By addressing these challenges, business incubators like Chemin can further bolster their support for startups, contributing to economic development and entrepreneurial growth. Lastly, this research adds valuable insights to the field of business incubation, offering practical recommendations for enhancing the effectiveness of resource allocation strategies. Through a nuanced understanding of how tangible and intangible resources impact incubate success, this study aims to inform policymakers, incubator managers, and entrepreneurs alike, fostering a conducive ecosystem for startup growth and innovation.
Keywords: Entrepreneurship; Intangible asset; Resource; Business incubators -- South Africa East London; New business enterprises -- South Africa